2010
DOI: 10.1007/s00467-010-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

A case of dense deposit disease associated with a group A streptococcal infection without the involvement of C3NeF or complement factor H deficiency

Abstract: A 14-year-old girl presented with acute glomerulonephritis. Tests revealed hypocomplementemia and elevated Antistreptolysin-O titers, and renal biopsy revealed endocapillary and mesangial proliferative glomerulonephritis with double contours of the glomerular basement membrane (GBM). Despite methylprednisolone pulse therapy and the administration of oral prednisolone, overt proteinuria and hypocomplementemia persisted. A second renal biopsy 6 months later confirmed the initial diagnosis of dense deposit diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…These findings further supported the possible involvement of a streptococcal infection. Glomerular NAPlr deposition has also been found in patients with glomerular diseases other than APSGN, including those with Henoch-Schönlein nephritis (HSPN), lupus nephritis, and dense-deposit disease [2,5,[7][8][9]. In a study of childhood HSPN cases, it was reported that 30% showed immunostaining for the glomerular NAPlr antigen [5].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings further supported the possible involvement of a streptococcal infection. Glomerular NAPlr deposition has also been found in patients with glomerular diseases other than APSGN, including those with Henoch-Schönlein nephritis (HSPN), lupus nephritis, and dense-deposit disease [2,5,[7][8][9]. In a study of childhood HSPN cases, it was reported that 30% showed immunostaining for the glomerular NAPlr antigen [5].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the nephritis-associated plasmin receptor (NAPlr), a nephritogenic antigen for APSGN, was isolated and is thought to be useful in the diagnosis of glomerulonephritis associated with streptococcal infection [2][3][4][5][6][7][8][9]. NAPlr is homologous to the group A streptococcus plasmin receptor known as streptococcal glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which is thought to impair glomeruli either directly or indirectly [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…They speculated that streptococcal skin infections, such as in their case, might preferentially induce subendothelial deposition in consideration of previous reports that showed that 7 of 27 patients with PSAGN associated with streptococcal pyoderma displayed subendothelial deposits (11). In addition, cases of dense deposit disease (DDD) associated with a group A streptococcus infection have been reported (4,5,10,12). Interestingly, the disease resolved in most of these patients with minimal treatment without the progression to end-stage renal failure despite persistently low serum C3 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Suga et al reported a case of DDD associated with a group A streptococcal infection without the involvement of C3NeF or CFH deficiency. In their case, NAPlr and plasmin activity in the glomeruli persisted 6 months after disease onset, which generally disappears within one month (5). They speculated that the persistent deposition of NAPlr might play a role in the development of DDD through the continuous trapping of immune complexes accompanied by complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, glomerular NAPlr deposition can be found with extraordinary frequency in early-phase APSGN patients. However, recent observation has revealed that glomerular NAPlr deposition and plasmin activity could be found in a similar fashion also in other glomerular diseases, such as dense deposit disease (DDD) [31, 32], Henoch-Schonlein Purpura nephritis (HSPN) [7, 33] and membranoproliferative glomerulonephritis (MPGN) [7], in which recent streptococcal infection has been suggested by serological tests. The histological characteristics common to these cases are prominent endocapillary proliferation.…”
Section: Glomerular Naplr Deposition In Other Glomerulonephritis Rmentioning
confidence: 99%